2020
DOI: 10.1111/adb.12871
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex dysfunction in problem gamblers

Abstract: Impairments in response inhibition have been implicated in gambling psychopathology. This behavioral impairment may suggest that the neural mechanisms involved in response inhibition, such as GABA A-mediated neurotransmission in the primary motor cortex (M1), are also impaired. The present study obtained paired-pulse transcranial magnetic stimulation markers of GABA A and glutamate receptor activity from the left M1 of three groups-problem gamblers (n = 17, 12 males), at-risk gamblers (n = 29, 19 males), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Similarly, Chowdhury, et al 20 reported a positive correlation between GABAergic transmission in the motor cortex and SSRTs. Interestingly, despite the absence of group differences in SST performance, Chowdhury, et al 20 also found evidence for reduced GABAA receptor activity and increased glutamate receptor activity in a GD sample compared to non-gamblers and at-risk gamblers, respectively. Additionally, exogeneous dopamine administration reduced prefrontal GABAA receptor availability less in treatment-seeking problem gamblers than in healthy volunteers 36 .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, Chowdhury, et al 20 reported a positive correlation between GABAergic transmission in the motor cortex and SSRTs. Interestingly, despite the absence of group differences in SST performance, Chowdhury, et al 20 also found evidence for reduced GABAA receptor activity and increased glutamate receptor activity in a GD sample compared to non-gamblers and at-risk gamblers, respectively. Additionally, exogeneous dopamine administration reduced prefrontal GABAA receptor availability less in treatment-seeking problem gamblers than in healthy volunteers 36 .…”
Section: Introductionmentioning
confidence: 82%
“…While response interference using the Flanker task has to our knowledge not yet been studied in populations with GD, previous research on problem gambling and response inhibition using the SST has produced mixed results. Inhibition-related variables, such as the SSD and SSRT, often do not dissociate between gambling and non-gambling participants [15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…In general, the relationship between ongoing corticospinal brain activity and behavioral motor functioning has been extensively investigated (Duque et al 2017). Recently, quite a few studies (Chowdhury et al 2018, 2019a, 2019b, 2020a, 2020b; He et al 2019; Hermans et al 2019) have investigated the relationship between offline TMS-derived GABAergic inhibitory biomarkers (resting-state SICI, LICI) and behavioral motor-inhibitory efficiency. In particular, in their study Chowdhury and Colleagues (2018) showed for the first time a negative correlation between individual GABA A ergic intracortical motor inhibition (measured via SICI’s amplitude) and SSRT’s length, indicating that subjects with stronger resting state SICI tend to be faster at inhibiting their responses, and so better at action stopping.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is still unclear whether individual differences in these neurophysiological markers of intracortical inhibition might be related to actual behavioral individual differences in inhibitory control efficiency (Chowdhury et al 2017; He et al 2019). Recently quite a few studies (Chowdhury et al 2018, 2019a, 2019b, 2020a, 2020b; He et al 2019; Hermans et al 2019) have investigated whether and to what extent individual levels of resting-state SICI and LICI measured offline might reflect individual differences in the efficiency of the inhibitory processes, indexed by the length of the SSRT. Taken together, these studies support the hypothesis that trait-like interindividual differences the neurophysiological markers of intracortical inhibition (and SICI in particular) can predict individual’s actual behavioral motor inhibition capacities (Chowdhury et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently extended the evidence for the involvement of SICI in stopping, showing that shorter SSRTs are correlated with stronger SICI (Chowdhury, Livesey, Blaszczynski, & Harris, 2020;Chowdhury, Livesey, & Harris, 2019a, 2019bChowdhury, Livesey, Blaszczynski, & Harris, 2018). In this study, we determined whether training participants in the stop signal task would lead to increased SICI strength.…”
Section: Introductionmentioning
confidence: 93%